First report of human infection caused by Colletotrichum chlorophyti occurring in a post-corneal transplant patient with endophthalmitis - Paniz-Mondolfi, Alberto E.; Agemy, Steven; Cañete-Gibas, Connie; Gitman, Melissa R.; Iacob, Codrin E.; Necula, Inna; Wang, Ching-Yi; Delgado Noguera, Lourdes A.; Sanders, Carmita; Wiederhold, Nathan P.; Sordillo, Emilia M.; Nowak, Michael D. (Medical mycology case reports, 2021)
Keratomycosis or mycotic keratitis is recognized as one of the major causes of ophthalmic morbidity worldwide. The most common organisms linked to keratomycosis include Candida spp., Fusarium spp., and Aspergillus spp. However, varieties of saprobic fungi have been reported as causative agents of keratomycosis. Amongst these are members of the genus Colletotrichum. Herein we present the first reported case of C. chlorophyti infection in a post-corneal transplant patient, suggesting an increasing role for Colletotrichum species as emerging human pathogens, particularly in the transplant population. •Keratomycosis is a major cause of ophthalmic morbidity and blindness worldwide.•Colletotrichum spp are increasingly recognized as etiologic agents of keratomycosis.•This is the first report of human infection by Colletotrichum chlorophyti.•Differentiation among the Colletotrichum species is phenotypically difficult, requiring further characterization at a molecular level.